STUDY ON METAPHORICAL EXPRESSIONS IN THE BOOK NGAWUR KARENA BENAR BY SUJIWO TEJO: A PRAGMATIC APPROACH - MEDINA, SABILA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Metaphor, Book Ngawur Karena Benar, Sujiwo Tejo This study concerns on metaphorical expressions / utterances in the book Ngawur Karena Benar written by Sujiwo Tejo and their nonliteral meaning. Infinding the metaphorical expressions, the writer used the theory of metaphor byStern (2000). Otherwise, in analysing the nonliteral meaning, the writer usedrelevance approach by Sperber and Wilson (1982). According to relevance theory, the process of interpreting a metaphorical expression comprises the following steps: decoding the linguistic input by arraying possible meanings of an utterance, drawing inferences by taking into account both the results of linguistic decoding, i.e. the logical form, and  assumptions taken from the context. The problems are to answer: 1) what metaphorical expressions can be found in the book Ngawur Karena Benar by Sujiwo Tejo, 2) what are the meaning of the metaphorical expressions used in the book Ngawur Karena Benar by Sujiwo Tejo.This study applied qualitative research method by employing documentanalysis approach to get detailed data description from the object analysis. Thedata of this study are the metaphorical expressions in the book Ngawur KarenaBenar by Sujiwo Tejo.Results of this study revealed that the metaphorical expressions are used todeliver a complicated circumstance in revealing the real condition. In line with the finding, the nonliteral meaning of the metaphorical expressiona needs anintralinguitics and extralinguistics factor. The intralinguistics factor is theinformation we can receive by decoding the linguistic input while theextralinguistics factor is the assumptions taken from context by drawinginferences.The last but not least, the writer suggests the next researchers who concernin the study of metaphorical expression in any media to observe in differentsetting and theoretical frameworks to enrich the study about metaphoricalexpression.